2017
DOI: 10.1002/2016ja023160
|View full text |Cite
|
Sign up to set email alerts
|

In situ statistical observations of Pc1 pearl pulsations and unstructured EMIC waves by the Van Allen Probes

Abstract: We present here the first in situ statistical survey of structured Pc1 pearl pulsations compared with unstructured electromagnetic ion cyclotron (EMIC) waves observed by the Van Allen Probes spacecraft. This data set was compiled from observations spanning 8 September 2012 through 31 August 2015 and comprises over 1630 h of total EMIC wave activity, of which 291 h exhibited pearl structure. Additionally, we have identified 29 wave events demonstrating periodically oscillating wave packets, mostly about the mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 56 publications
5
35
0
Order By: Relevance
“…The frequency range of the fine‐structured EMIC wave is observed to be approximately constant and is not confined between the equatorial ion cyclotron frequencies. This is consistent with that observed in previous reports (e.g., Paulson et al, ) and indicates that the waves are generated by a mechanism that is different from that of local ion cyclotron instability. The wave intensity was about 10 −3 mV 2 /m 2 /Hz, which is relatively small compared to typical EMIC waves observed in the inner magnetosphere.…”
Section: Observationssupporting
confidence: 93%
See 2 more Smart Citations
“…The frequency range of the fine‐structured EMIC wave is observed to be approximately constant and is not confined between the equatorial ion cyclotron frequencies. This is consistent with that observed in previous reports (e.g., Paulson et al, ) and indicates that the waves are generated by a mechanism that is different from that of local ion cyclotron instability. The wave intensity was about 10 −3 mV 2 /m 2 /Hz, which is relatively small compared to typical EMIC waves observed in the inner magnetosphere.…”
Section: Observationssupporting
confidence: 93%
“…Paulson et al () also discriminated the observed EMIC waves based on the structures of their spectra, and they found that the local‐time distributions of unstructured and fine‐structured EMIC waves are different. They pointed out that the observed fine‐structured EMIC waves have no distinct local‐time dependence in the equatorial plane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figures c and d present structured H + band EMIC waves from 1118 to 1210 UT, representing a long duration event. These structured EMIC waves are called “pearl structures” (e.g., Jun et al, , ; Paulson et al, ) that have often been observed during quiet geomagnetic conditions in the morning sector within the inner magnetosphere (Paulson et al, ). During this EMIC event, we can see a clear H + flux enhancement at 0.1–1 keV (Figure e).…”
Section: Observationsmentioning
confidence: 99%
“…This event does not belong to the class of “pearl” events identified by Paulson et al . [, ] in that it does not show any periodic temporal modulation. Nevertheless, it is similar to them in that those events at times exhibited a nearly constant frequency across L shells.…”
Section: Examples Sorted By Storm Phasementioning
confidence: 99%